Low holo-transcobalamin levels are prevalent in vegetarians and is associated with coronary artery disease in Indian population. (3rd July 2016) - Basak, Trayambak; Garg, Gaurav; Bhardwaj, Nitin; Tanwar, Vinay Singh; Seth, Sandeep; Karthikeyan, Ganesan; Sengupta, Shantanu
Abstract: Coronary artery disease (CAD) has been increasing alarmingly in India. We had earlier shown that vitamin B12 deficiency is associated with CAD in Indian population. However, only about a quarter of the total vitamin B12 is internalised in the cells by the proteins transcobalamin II. Vitamin B12 -bound transcobalamin II (holotranscobalamin, holoTC) is thus referred to as biologically active B12 . In this study, we ascertained the levels of holoTC in 501 CAD cases and 1253 healthy controls and for the first time show that holoTC levels are significantly lower ( p  = 2.57E-4) in CAD (26.81 pmol/l) cases as compared to controls (29.97 pmol/l).